Langerhans cell histiocytosis in a 3-year-old girl: a case report and literature review - Duda-Szymańska, Joanna; Wierzchniewska-Ławska, Agnieszka (Polish Journal of Pathology, 2009)
The report presents a case of Langerhans cell histiocytosis with diagnostic problems and fatal outcome in a 3-year-old girl, as well as a short literature review.